Las antinomias jurídicas de la ley orgánica de transporte terrestre y seguridad vial respecto de los delitos de tránsito contemplados en los art. 131 y 132 . Necesidad de su reforma para su correcta aplicación - Quizhpe Donoso, Nelson Rodrigo (2014)
This thesis entitled "THE ORGANIC LAW OF THE LEGAL LAND TRANSPORT AND ROAD SAFETY antinomies RESPECT OF TRAFFIC OFFENSES LISTED IN ART. 131 and 132. NEED FOR REFORM FOR PROPER APPLICATION "'s main purpose is to analyze the relationship between the penalty and prosecution of traffic violations specifically crimes and violations, their impact on the injury of the legal rights of people because of perpetration a violation and impunity in the trial of those offenses. In the field of traffic, the injured legally must be analyzed from two perspectives, as the endangerment of individual legal interests leads to think that the issue of transit, is a means or instrument of protection of other pressing and core resources as the are the life, physical integrity of persons, free movement and mobility and secondly no less important public or private property, due process and legal certainty, not an end in itself, ie, that first what the law protects the life, health and physical integrity of people and goods through penalty and prosecution of those behaviors that develop in the traffic. Also, this work has had its full theoretical foundation that has served to strengthen the information obtained; the methods used are: inductive method in order to examine specific aspects such as the violation of the legal rights, legal exegetical methods allowed an analysis and reflection on the legal rules, analytical method is able to study the problem from the point of view social, legal, political and even economic finally the synthetic method by compiling bibliographies to argue the subject of study; between the main results were obtained: By applying the interview and survey of the legal profession and the manifestation of discontent legal uncertainty is established and as such the system of justice in terms of the sanction and prosecution of offenses and traffic offenses. Traffic offenses are the offenses of culpable nature committed against the regulations governing vehicular traffic or because the agent that causes it is not intended to cause harm but nevertheless occurs, negligence, recklessness, incompetence and failure, it that makes him worthy of reproach state and society for their lack of caution or care and the respective penalty laws which carries a penalty either economic or custodial type. In the field of traffic, the injured legally must be analyzed from two perspectives, as the endangerment of individual legal interests leads to think that the issue of transit, is a means or instrument of protection of other pressing and core resources as they are the life, physical integrity of persons, free movement and mobility, public or private property through suppression of dangerous behaviors that develop in the traffic. In that sense, the issue of transit is not only a particular segment of public safety but also of legal certainty, however, traffic laws of our country in the manner prescribed for the punishment and prosecution of traffic offenses provided in Arts. 131 and 132 leave the possibility that these crimes go unpunished because of the contradictions and / or existing regulatory gaps.